PENGEMBANGAN MODEL MANAJEMEN KURIKULUM BERBASIS PENGUATAN PENDIDIKAN KARAKTER UNTUK MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH DASAR - Subekti Kusumadewi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this research is to solve the problems in elementary schools especially in the application of learning that still does not prioritize character education.This research methods is a type of research and development with reference to Borg and Gall model with only seven steps, including: (1) potential and problems, (2) data collection, (3) product design, (4) product validation, (5) revision products, (6) product trials, and (7) product revision. Data obtained through observation, interviews, questionnaires, and documentation. Sources of data are Class IV students and Class IV teachers at Masehi Kudus Elementary School, Tanwirul Qulub School, and 2nd Panjunan School.The results of the effectiveness test show that “Curriculum Management Based on Strengthening Character Education for Improving the Quality of Learning in Elementary Schools is effectively used in learning in Class IV Elementary Schools Theme “Beautiful Togetherness” Sub Theme 1 “Diversity of My Nation’s Culture” with the average results of individual completeness in Masehi Elementary School reaches 91%, while in Tanwirul Qulub Elementary School and 2nd Panjunan Elementary School reached 82%. The classical completeness of the three elementary schools is also very high with an average classical completeness of almost 100%. The classical completeness in the three elementary schools in a row is at Masehi Kudus Elementary School reaching 100%, at Tanwirul Qulub Elementary School and 2nd Panjunan Elementary School are reaching 95%. Classical absorption is also relatively high with the acquisition in each elementary school as follows: at Masehi Kudus Elementary School by 91%, at Tanwirul Qulub Elementary School and 2nd Panjunan Elementary School by 82%.